The usability and technology acceptance of immersive virtual reality simulation for critical infrastructure workers - Andrzej Grabowski (Edukacja Ustawiczna Dorosłych)
One of the main applications of Virtual Reality (VR) in critical infrastructure is training. Training is crucial for ensuring the safety, security, and efficiency of critical infrastructure systems and their employees. VR can also be used to train critical infrastructure personnel responsible for ensuring CI business continuity and disaster recovery. However, there is little research on how such an immersive virtual simulation can affect critical infrastructure staff especially in terms of usability and acceptance of the technology, as this is very important for practical implementation. For this reason, the research was carried out with 20 experts active in various critical infrastructure facilities. In addition to the usability and technology acceptance, the level of simulator sickness, the realism of the simulation, the workload and stress caused by the training tool, as well as an overall assessment of the training quality were examined. The very high score for the indicators of intention to use, perceived usefulness, and engagement (around 90% of the maximum value) is particularly important. This indicates that the vast majority of end users should be willing to use the VR training simulations developed